(untitled) (Research, Society and Development, 2021)
Currently, music is present in almost all social spaces, but this does not mean that it contributes to increase the quality of thought formation and aesthetic feeling of people. Music is used to entertain and to pass the time, but it hardly promotes fruition. In light of the above, this study aims to examine how music has been used by the cultural industry to format men’s hearing, contributing to the regression of hearing. It is a qualitative research and the method used is the critical-dialectical of theoretical nature, based on bibliographic sources that support the discussion of the concepts. First, it discusses musical taste, which is often conditioned by production relations, emphasizing how music - as well as other artistic languages - has been co-opted by instrumental reasoning. In sequence, it shows how music on an industrial scale has contributed to format the hearing of individuals, who are used to the same musical chords, with no variation of timbers, pointing out the negativity of this situation, because it can also contribute to the aesthetic formation. It is concluded that there is a distance between musical success and its aesthetic quality. Philosophically, music has a negative potentiality that makes it possible not only to be heard in moments of leisure, but it can also provide an aesthetic experience, resulting in a formative act.